Teachers’ Teaching Practices and Students’ Self-Concept in Relation To Problem-Solving Performance - Shaira Faye T. Bohol; Genelyn R. Baluyos (PT ARRUS Intelektual Indonesia, 2023)
The teachers’ teaching practices and the students’ self-concept play a vital role in the performance of students in Mathematics. This study explored the extent of Mathematics teachers' teaching practices and the level of the students' self-concept toward mathematics in relation to problem-solving performance. It was conducted on a total of 111 Grade 10 students who participated in the limited face-to-face classes in all secondary schools in District 10 of the Division of Ozamiz City. This study employed a descriptive-correlational research design. Questionnaires and a problem-solving test were utilized in gathering the data that were analyzed and interpreted using Mean, Standard Deviation, Pearson Product-Moment Correlation Coefficient, and Stepwise Multiple Regression Analysis. Results showed that the Mathematics teachers' teaching practices were demonstrated to a great extent. The students have a fair level of learned self-concept, organized self-concept, and a good level of dynamic self-concept. However, the students' performance in problem-solving did not meet the expectations of the standards set by the DepEd. It was found that there was a significant relationship between the teachers' use of mathematical representations in teaching and the students' problem-solving performance in Mathematics. Furthermore, there was a significant relationship between students' dynamic self-concept and problem-solving performance. The use of mathematical representations of teachers and students' dynamic self-concepts were the predictors of students' problem-solving performance.